Jawabanmu

2014-06-16T15:55:40+07:00
Cosx - Sinx = k
(Cosx - Sinx)² = k²
Cos²x + Sin²x - 2SinxCosx = k²
           1      -      2SinxCosx = k²
                          2SinxCosx = 1 - k²
Cos2x = Cos²x - Sin²x
           = (Cosx + Sinx)(Cosx - Sinx)
           = k(Cosx + Sinx)
(Cos2x)² = k²(Cosx+Sinx)²
              = k²(Cos²x+Sin²x+2SinxCosx)
              = k²(1 + 1 - k²)
              = k²(2-k²)
Cos2x    = √{k²(2-k²)}
              = k√(2-k²) dengan syarat -√2 ≤ k ≤ √2  supaya tidak imajiner